KESESUAIAN WILAYAH BUDI DAYA IKAN KERAPU BERDASARKAN CITRA SATELIT LANDSAT-8 OPERATIONAL LAND IMAGER (OLI)/THERMAL INFRARED SENSOR (TIRS) (STUDI KASUS PERAIRAN KECAMATAN GEROKGAK, KABUPATEN BULELENG, PROVINSI BALI) - Azizah, Febiana Nur; Afgatiani, Pingkan Mayestika; Adawiah, Syifa Wismayanti; Anggraini, Nanin; Ginting, Devica Natalia Br; Patwati, Ety; Asriningrum, Wikanti (Institut Teknologi Sepuluh Nopember, 2021)
he waters in Gerokgak District are one of the aquatic region in Indonesia that have potential as regional land for the development of aquaculture, one of which is grouper cultivation. To increase the potential of grouper cultivation, it is necessary to know the right location of grouper cultivation. This study applies a method using an overlay between oceanographic parameters, namely sea surface temperature (SST), salinity, chlorophyll, and Total Suspended Solid (TSS). In addition, this study also uses a remote sensing approach by utilizing Landsat-8 Operational Land Imager (OLI) and Thermal Infrared Sensor (TIRS) satellite imagery data. The results of this study indicate that the waters in the Teluk Penerusan, Gerokgak District, Bali have waters that are suitable for grouper cultivation. Based analysis result between the values of sea surface temperature and chlorophyll with in situ values, it shows good accuracy with values of R2 = 0,661; 0,686 for chlorophyll in situ, and 0,658 for TSS with in situ.